Leveraging aerial and underwater drones and corporate social responsibility to secure Nigeria's oil and gas sector: enhancing crude oil production and strengthening national economic growth - Enisuoh, W.; Pondi, K.; Tangbe, P. (Offshore Technology Conference, 2026)
Nigeria's oil and gas sector remains central to national revenue generation and economic stability, yet its performance has been persistently undermined by crude oil theft, pipeline vandalism, operational inefficiencies, and environmental degradation, particularly in the Niger Delta. These challenges have constrained crude oil production, weakened investor confidence, and limited the sector's contribution to national economic growth. This study examines how integrating aerial and underwater drone technologies with corporate social responsibility (CSR) initiatives can enhance the security, efficiency, and sustainability of Nigeria's oil and gas operations. Table 1 shows Nigeria's crude oil production from 2020 to 2025. These figures combine crude oil and condensate averages where available, and in some markets (like OPEC reporting) exclude condensate, which can affect comparability. The data show an overall downward trend from 2019 peak levels, but gradual stabilization and partial recovery between 2023 and 2025. Using a qualitative analytical approach based on secondary data from academic literature, policy reports, and industry assessments, the study explores the role of aerial drones in monitoring onshore and nearshore pipeline networks, detecting illegal activities, and providing real-time intelligence, as well as the contribution of underwater drones—such as remotely operated vehicles (ROVs)—in inspecting submerged pipelines, detecting leaks, and reducing undetected production losses. The study further situates these technological interventions within a CSR framework that addresses host-community grievances through employment, livelihood support, environmental remediation, and inclusive stakeholder engagement.
Keywords: Corporate social responsibility; Drone; Livelihood; Petroleum industry; Pipeline transport; Production (economics); Revenue; Stakeholder; Sustainability

The risk and time course for autoimmune rheumatic disease development in patients with Raynaud phenomenon - Teaw, Shannon; Shojaee, Abbas; Carnaru, Miruna; Hinchcliff, Monique (The Journal of Rheumatology, 2025)
The prevalence of Raynaud phenomenon (RP), defined as skin color changes on acral body segments in response to cold or stress, has been estimated to be 3-5% in population studies.1,2 In 80-90% of cases, patients are otherwise healthy and are diagnosed with primary RP.1,3
Keywords: Autoimmune disease; Dermatology; Disease; Immunology; Immunopathology; Internal medicine; Medicine; Phenomenon; Rheumatic disease; Rheumatology; Systemic disease

The price and quality of methylphenidate products - Narayan, Aditya; Teasdale, Ben; Hudspeth, Amber; Light, David; Nailor, Jill; Schulman, Kevin (Journal of the American Academy of Child & Adolescent Psychiatry, 2025)
Keywords: Attention deficit hyperactivity disorder; Business; Methylphenidate; Philosophy; Psychiatry; Psychology; Quality (philosophy)

Quality of experience aware secure mobility management in 6G hybrid edge quantum blockchain networks - Laboni, Nadia; Razzaque, Abdur; Sharmin, Selina; Alelaiwi, Abdulhameed; Hassan, Rafiul; Hassan, Mohammad (SSRN Electronic Journal, 2025)
Keywords: Cryptography; Edge computing; Handover; Mobile edge computing; Mobility management; Quality of service; Task (project management); Wireless; Wireless network

A gated transformer MADDPG algorithm for latency and energy aware task offloading in digital twinning aerial edge computing - Sami, M.; Tanvir, Ibrahim; Roy, Palash; Razzaque, Abdur; Hassan, Rafiul; Hassan, Mohammad (SSRN Electronic Journal, 2025)
Keywords: Edge computing; Edge device; Efficient energy use; Energy consumption; Latency (audio); Mobile edge computing; Task (project management); Task analysis

The Making of a Puritan Mediator. - Smith, Leann E. (Fall., 1992)
Keywords: faculty_collection; sabbatical_report; unidentified

African American Connecticut explored - Normen, Elizabeth J. (Garnet books, 2013)
First book for a general readership to present an overview of the African American experience in Connecticut
Keywords: African Americans; Biography; Connecticut; History; African Americans; faculty_collection; unidentified

In a Fine Frenzy: Poets Respond to Shakespeare - Starkey, David; Willis, Paul J. (University of Iowa Press, 2005)
Showcasing poems by more than ninety contemporary American poets, In a Fine Frenzy reveals what Shakespeare's poetic children have made of their inheritance. Particularly interested in Viola, Miranda, Prospero, Desdemona, Iago, Lear, Cordelia, Hamlet, Horatio, and Ophelia, the poets respond to the sonnets, the comedies, the tragedies, the romances, and, to a lesser degree, Shakespeare the man. In so doing they reveal the aspects of his work most currently captivating to modern writers. Those who cherish Shakespeare's mercurial wit will delight in the rapid shifts, from grief to hilarity, so characteristic of the bard himself. Comic poems about tragedies follow decidedly somber poems about comedies. Single poems contain multiple emotional twists and turns. Some pay homage; most interact directly with the original Shakespearean text. Collectively, they corroborate Ben Jonson's assertion that Shakespeare is "not of an age, but for all time."--(Source of description unspecified.)
Keywords: 20th century; 21st century; American poetry; Poetry; American poetry; Shakespeare, William, 1564-1616; faculty_collection; unidentified

Genre by Example: Writing What We Teach - Starkey, David (Boynton/Cook Publishers-Heinemann, 2001)
Keywords: English language; Rhetoric; Study and teaching (Higher); Creative writing (Higher education); Literary form; Study and teaching; Report writing; faculty_collection; unidentified

Taking Stock: The North American Livestock Census - Bixby, Donald E.; American Livestock Breeds Conservancy (McDonald & Woodward Pub. Co., 1994)
Keywords: Canada; Canada; Livestock breeds; Germplasm resources; Livestock; United States; Livestock; United States; Livestock breeds; faculty_collection; unidentified

Words for My Daughter: Poems - Balaban, John (National poetry series, 1991)
Keywords: faculty_collection; unidentified

The Education of Women in Eighteenth-Century Germany: New Directions from the German Female Perspective: Bending the Ivy. - Petschauer, Peter (1989)
Keywords: 18th century; Education; Germany; History; Women; faculty_collection; unidentified

The Red Envelope: Poems - Russell, CarolAnn (Contemporary poetry series (Orlando, Fla.), 1985)
Keywords: faculty_collection; unidentified

Working Bibliography of the Bald Eagle. - Lincer, Jeffrey L.; Clark, William S.; LeFranc, Maurice N. (1979)
Keywords: Bald eagle; Bibliography; Bibliography; Birds; faculty_collection; unidentified

Mabryettes - Mabry, Edward Loughlin (E.L. Mabry, 1978)
Keywords: faculty_collection; unidentified

Guide to Grants - Erway, Milton K.; Murphy, Edward J. (SCSC Foundation, 1977)
Keywords: Directories; Directories; Educational fund raising; Research grants; faculty_collection; unidentified

Clearings and Favors ; Poetry and Prose - Harding, May (Dunaway Press, 1976)
Keywords: faculty_collection; unidentified

Speaking Is a Practical Matter - McCabe, Bernard P.; Bender, Coleman C. (Holbrook Press, 1976)
Keywords: Oral communication; dept.com; faculty_collection

The Spanish Teenager - Bourque, Jane M.; Allen, Eva Llorens; Briggs, Sandra Marceau (Foreign culture series, 1974)
Keywords: Spain; Youth; faculty_collection; unidentified

I See the Line of My Life; Poems. - Harding, May (Dunaway Press, 1973)
Keywords: faculty_collection; unidentified

Pembroke. - Freeman, Mary Eleanor Wilkins (Masterworks of literature series, 1971)
Keywords: Fiction; New England; dept.eng; faculty_collection

Neo-Sumerian account texts from Drehem. - Keiser, Clarence Elwood; Kang, Shin Theke (Babylonian inscriptions in the collection of James B. Nies, Yale University ; v. 3, 1971)
Keywords: Commerce; Drehem (Extinct city); Sumerian language; Texts; Babylonia; dept.his; faculty_collection

The Wish to Be Free; Society, Psyche, and Value Change - Weinstein, Fred; Platt, Gerald M. (University of California Press, 1969)
Keywords: Social change; Authority; Personality and culture; faculty_collection; unidentified

Flexible Scheduling, - Educational Research Council of America Department of In-service Education and Staff Utilization (Educational Research Council of America, 1968)
Keywords: Schedules, School; School management and organization; dept.edu; faculty_collection

Speaking Is a Practical Matter - McCabe, Bernard P.; Bender, Coleman C. (Holbrook Press, 1968)
Keywords: Oral communication; dept.com; faculty_collection

Introductory Numerical Analysis - Pettofrezzo, Anthony J. (Heath, 1967)
Keywords: Numerical analysis; faculty_collection; unidentified

Switzerland, Present and Future: A Small Country Re-Examines Itself - Nouvelle Société helvétique (Jahrbuch der Neuen Helvetischen Gesellschaft, 1963)
Keywords: Switzerland; faculty_collection; unidentified

The Federal Constitution Celebration in Pennsylvania, 1937-1938. - Pennsylvania Constitution Commemoration Committee (Pennsylvania Constitution Commemoration Committee, 1938)
Keywords: United States. Constitution; faculty_collection; unidentified